Development of a competency-based clinical assessment instrument for exit level Oral Hygiene students at the University of Western Cape - M. Naidoo; P. Brijlal; R. Cader; N. A. Gordon; C. A. Rayner; K. Viljoen (BMC, 2022)
Abstract Seminal to the process of a health sciences curriculum evaluation is the periodic review of clinical assessment instruments that measure competency. An assessment of quality is facilitated by using a well-structured, authentic and reliable instrument. This process rests on designing and measuring the instrument against a sound framework and validating it for scientific merit. This paper documents the pedagogy and the process taken in developing an improved formative competency-based assessment instrument for the final year students of the Bachelor of Oral Health program (BOH) at the University of the Western Cape (UWC). Methods: A qualitative research study design employing the Nominal Group Technique (NGT) was used as a method for gaining small group consensus on the clinical assessment instrument for exit level Oral Hygiene (BOH3) students within the parameters of assessment principles. The key contributors to the instrument development process were the academic staff of the Department of Oral Hygiene, involved in clinical teaching and assessment of student competency. Results: The domains of ethics and professionalism, patient assessment, diagnosis, treatment planning and implementation was identified as the core elements in the assessment. The principles of assessment, which include, alignment with outcomes, feedback, transparency and validity, were used to guide the instrument development. The assessment criteria were cross examined for alignment to the learning outcomes of the module and the program whilst formative feedback was foregrounded as a central feature to support student learning and progress monitoring. Transparency was obtained by providing students access to the instrument before and after the assessment including the written feedback on their performance. The instrument embodied a range of criteria to be assessed rather than on the awarding of a cumulative score. This allowed for the identification of the criteria or domain within which a student is struggling or excelling. Consensus on the instrument design was achieved using the NGT phases throughout the instrument development process including the weighting of the domains and grading. This level of engagement together with the application of scientifically sound assessment principles contributed to the validation of the instrument. Conclusion: The development of a competency-based assessment instrument was the result of a structured, collaborative and scientifically engaged process framed around specific assessment principles. The process culminated in the development of a formative competency-based clinical assessment instrument that was fit for purpose in the Bachelor of Oral Health program. The Nominal Group Technique served to be a valuable approach for small group consensus in developing the instrument. It served to promote individual perspectives and to generate debate and group discussion between academics that were proficient in clinical teaching and, finally to facilitate group consensus on the instrument structure and system for administration.